Selected Abstracts of the 6th International Congress of UENPS; Valencia (Spain); November 23rd-25th 2016; Session “Other organs (eye, kidney, blood)” - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2016)
Selected Abstracts of the 6th International Congress of UENPS; Valencia (Spain); November 23rd-25th 2016; Session “Other organs (eye, kidney, blood)” ABS 1. NEPHROLITHIASIS IN AN EXTREMELY LOW BIRTH WEIGHT INFANT. A CASE REPORT • R. Garunkstiene, R. Vaitkeviciene, I. Paulaviciene ABS 2. A CASE OF SEVERE HEMOLYTIC DISEASE DUE TO Rh-ISOIMMUNIZATION • M. Anselmo, P. Mendes, P. Cruz, L. Gonçalves ABS 3. TENDENCY OF RETINOPATHY OF PREMATURITY. ARE OUR PRETERM BABIES SAFE FROM IT? • P. Priego, M.J. Parraga, I. Tofe ABS 4. TRANSIENT ABNORMAL MYELOPOIESIS AND HYDROPS FETALIS WITH DOWN SYNDROME IN A PRETERM INFANT AND ABNORMAL PLACENTAL FINDINGS • O. Turan, D. Anuk Ince, L. Olcay, S. Agva, O. Ote, Z. Yılmaz Çelik, A. Ecevit ABS 5. BLOOD TRANSFUSIONS: INDICATIONS AND COMPLICATIONS IN THE NEONATAL INTENSIVE CARE UNIT OF CAIRO UNIVERSITY PEDIATRIC HOSPITAL • A. El-Badawy, A. Abdel-Razek, A. Tosson, M. Samaha ABS 6. EARLY TREATMENT OF HYPERBILIRUBINAEMIA WITH INTRAVENOUS IMMUNOGLOBULINS IN ABO OR Rh ISOSENSITIZATION OF THE TERM NEWBORNS • D. Zolger, J. Zolger ABS 7. EVALUATION OF INCIDENCE AND RISK FACTORS FOR RETINOPATHY OF PREMATURITY (ROP) IN GREEK PREMATURE INFANTS • M. Iordanidou, I. Spanopoulou, A. Boudakova-Esebidou, A. Konstantinidis, M. Skordala-Riti ABS 8. EVALUATION OF CORRELATION BETWEEN PRENATAL AND POSTNATAL ULTRASONOGRAPHIC FINDINGS OF URINARY TRACT DILATION • M.D. Ordónez Díaz, D. Trassierra Molina, M.V. Rodriguez Benitez, MP. Priego Ruiz, I. Tofé Valera, P. Jaraba Caballero, M.D. Ruiz González, J.L. Pérez Navero, E. Rogriguez Cano ABS 9. NEONATAL ALLOIMMUNE THROMBOCYTOPENIA DUE TO MATERNAL ANTI-HLA B49 AND CREG BW4 ANTIBODIES: A CASE REPORT • M. Fossati, L. Ilardi, G. Lando, S. Lo Pò, L. Sica, S. Martinelli ABS 10. DEEP VEIN THROMBOSIS IN A LATE PRETERM: A CASE REPORT • L. Blaga, M. Matyas, C. Vidra, M. Hasmasanu, G. Abrudan, A. Ciubotariu, G. Zaharie ABS 11. RED BLOOD CELLS TRANSFUSIONS IN VERY LOW BIRTH WEIGHT NEONATES • C. Pinto Marinho, H. Soares, F. Flor-de-Lima, H. Guimarães ABS 12. MAINZER-SALDINO SYNDROME: A RARE CAUSE OF CONGENITAL RENAL FAILURE • L. González, J. Martín, M. Gormaz, ML. Matoses, S. Mendizabal ABS 13. NEONATAL ALLOIMMUNE THROMBOCYTOPENIA: TWO CASE STUDIES • J. Borošak, J. Dodig, N. Šarlić, J. Tumbri, L. Mihovilović Prajz, R. Ribičić, D. Sović, M. Tomičić, A. Jularić ABS 14. NEONATAL HEMOLYTIC ANEMIA REVEALED BY EFFUSION SYNDROME: REPORT OF TWO CASES • N. Baddouh, N. Idrissi Slitine, S. Elmzah, F. Bennaoui, F.M.R. Maoulainine ABS 15. ABOUT A RARE CASE OF NEONATAL VOLKMANN SYNDROME REVEALING NEONATAL THROMBOPHILIA • L. Habibi, N. Idrissi Slitine, F. Elalouani, F. Bennaoui, F.M.R. Maoulainaine ABS 16. FUNCTIONAL STUDY OF THE KIDNEY TUBULES IN IUGR NEWBORNS, USING NGAL, THE NOVEL BIOMARKER OF KIDNEY INJURY • A.A. Akhundova, S.Sh. Hasanov, N.F. Panakhova, N.N. Hajiyeva ABS 17. POSTNATAL OUTCOME OF ANTENATALLY DIAGNOSED RENAL PELVIS DILATATION: A RETROSPECTIVE STUDY • S. Vora, N. Kavalloor, T.L. Yap, V. Rajadurai ABS 18. POLYCYTHEMIA. RISK FACTORS, MORBIDITY AND TREATMENT BEFORE AND AFTER BIRTH GUIDE CHANGE • V. Galán, R. Martín, C. Menéndez, M. Fariñas, R. Moreno